Idiopathic Lipoid Pneumonia: An incidental finding in autopsy specimen - Deepshikha Rana; Nidhi Kaushik; Shreya Sadhu; Rajnish Kalra; Rajeev Sen (University of São Paulo, 2020)
Lipoid pneumonia is a rare form of pneumonia which was initially described to be caused by inhalation or aspiration of fatty substances. Certain autopsy studies have reported the incidence to be 1.0-2.5%. Based on the mode of lipid acquisition, it has been classified into endogenous, exogenous or idiopathic types. Almost 50% of the patients with lipoid pneumonia are asymptomatic, and may be discovered by chance during routine chest imaging. In symptomatic patients, the symptoms are non- specific. However, it can produce inflammatory pneumonitis that can progress to irreversible pulmonary fibrosis as seen in our case. We present a case of a 53-year-old deceased male. A piece of one of his lungs was received after autopsy, which appeared normal grossly. There was no history of any illness before death. Microscopy revealed interstitial fibrosis with collection of foamy macrophages in alveolar spaces and cholesterol crystals surrounded by inflammatory reaction including occasional giant cells. The clinical picture and radiologic changes in cases of lipoid pneumonia can mimic bacterial pneumonia and tuberculosis. The occupational history is of extreme importance and should always be investigated.